Improvement of Organizational Citizenship Behavior (OCB) Assessed From Procedural Trust and Justice - Haki Rodian; Sumardi Sumardi; Henny Suharyati (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The quality of teacher services is an important element related to achieving national education goals and developing Indonesian people as a whole. The initial survey of teacher service quality in the Civil Servants in the High School in the city of Bogor has not yet reached maximum results. Therefore, the quality of teacher services is interesting to study. This study aims to find efforts to improve teacher service quality by examining the relationship of teacher service quality with teacher personality variables and organizational justice. Design/methodology/approach: The study uses correlational statistical methods and analysis of the sitorem method is conducted. The unit of research analysis was a high school civil servant teacher with a population of 279 and a sample of 103 teachers.. Findings: Analysis Results there are 9 indicators that the condition is good so it remains to be maintained, namely: (1) sincerity (2) enthusiasm (3) consensus (4) interpersonal justice (5) informational justice (6) distributive justice (7) physical appearance (8) ) guarantee (9) reliability. Components that are the order of priority indicators are improved, namely: (1) stable emotions (2) open to experience (3) procedural fairness (4) responsiveness (5) attention. Research limitations/implications: The results of the study show there is a positive relationship between the teacher's personality and the quality of teacher services with the strength of the relationship ry1 = 0.421 and there is a positive relationship between organizational justice and the quality of the teacher's service with the strength of the ry2 = 0.297 so that the quality of teacher service can be improved through the personality of the teacher and organizational justice.. Practical implications: To improve the quality of service teachers can pay attention to indicators that are not optimal for recommendations and determine the order of priority improvements that need to be done. Paper type: Research Paper